MENINGKATKAN KUALITAS PEMBELAJARAN GURU MATEMATIKA SMA/SMK BINAAN MENGGUNAKAN ACTIVE SHARING KNOWLEDGE - Giyarsih Giyarsih (Faktor Jurnal Ilmiah Kependidikan, 2015)
Abstract: The purpose of this study is to describe efforts to solve the problems found in theacademic supervision of Teachers of Mathematics in schools built. Knowledge Sharing Activelearning procedures, and classroom management.Results assistance to ten math teacherguidance, the authors conclude that the teachers of mathematics in Kulon Progo was stillvery need assistance from supervisors, especially regarding the implementation process ofinnovative learning, methods Active Sharing Knowledge to optimize the activity teachers andstudents from the beginning to the end of learning, improving the quality of the learningprocess. The magnitude of the increase is as follows. Active Knowledge Sharing by 5%. Themagnitude of the increase in activity of students reached 46%, while increasing mastery ofmathematical concepts reached 14%. Obtained a positive reflection of the results of theimplementation of learning facilitation Teachers of Mathematics with Active KnowledgeSharing by 84% agree and strongly agree.Keywords: Active Sharing Knowledge, Learning Quality Improvement, Assistance